2017
DOI: 10.1038/s41598-017-09372-1
|View full text |Cite
|
Sign up to set email alerts
|

Giant modulation of the electronic band gap of carbon nanotubes by dielectric screening

Abstract: Carbon nanotubes (CNTs) are a promising material for high-performance electronics beyond silicon. But unlike silicon, the nature of the transport band gap in CNTs is not fully understood. The transport gap in CNTs is predicted to be strongly driven by electron-electron (e-e) interactions and correlations, even at room temperature. Here, we use dielectric liquids to screen e-e interactions in individual suspended ultra-clean CNTs. Using multiple techniques, the transport gap is measured as dielectric screening … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 39 publications
(63 reference statements)
1
20
0
Order By: Relevance
“…A previous study of suspended m-CNTs in dielectric liquids showed that the gap is modulated by dielectric environment. 22 As noted in a number of previous experimental studies, m-CNTs with gaps of order 100 meV cannot be explained by non-interacting-electron band theory. 10,22,34,35 Non-interacting theories predict that m-CNTs have a small band gap due to curvature, axial strain, or twist.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…A previous study of suspended m-CNTs in dielectric liquids showed that the gap is modulated by dielectric environment. 22 As noted in a number of previous experimental studies, m-CNTs with gaps of order 100 meV cannot be explained by non-interacting-electron band theory. 10,22,34,35 Non-interacting theories predict that m-CNTs have a small band gap due to curvature, axial strain, or twist.…”
Section: Discussionmentioning
confidence: 91%
“…Theoretical models describing the transport gap of m-CNTs include enhancement of a bare band gap, 22 the opening of a Mott gap, 7,9,[11][12][13][14] and the opening of an excitonic insulator gap. 17 These theories make a variety of predictions regarding the diameter and chiral angle dependence of the gap.…”
Section: Introductionmentioning
confidence: 99%
“…Note that the fabrication for device D was slightly different and follows the method presented in Ref. 20. The magnitude for both devices decreases monotonically with filling.…”
Section: Measurement Summary For Devices B C and Dmentioning
confidence: 99%
“…Theory says that metallic nanotubes can develop a band gap due to symmetry breaking of the underlying graphene lattice from strains, twists and curvature. The magnitude of this gap is predicted to be around tens of milli-electron volts but zero field gaps of an order of a magnitude larger have been reported [19][20][21]. Perhaps most intriguingly though, in the single particle picture, these gaps should vanish at the Dirac field as the nanotube quantization line is pushed to the Dirac point of the underlying graphene band structure resulting in a truly metallic nanotube.…”
mentioning
confidence: 97%
“…Recent experiments suggested signatures of the EI phase in TiSe 2 in the 1T phase . Also, metallic carbon nanotubes can be seen as SMs, thus are candidates to host an EI phase . There are also investigations of Ta 2 NiSe 5 as a host material for the EI phase .…”
Section: Introductionmentioning
confidence: 99%